Experimental investigation of efficient and simple wind-turbine based on DFIG-direct power control using LCL-filter for stand-alone mode. (June 2022) - Amrane, Fayssal; Francois, Bruno; Chaiba, Azeddine
Abstract: This paper suggests an experimental implementation study of the Wind Energy Conversion System (WECS) based on efficient Direct Power Control (DPC). Stand-alone mode for variable wind speed application using Doubly-Fed Induction Generator (DFIG) is studied and developed in this work. Due to the wind power performance limitation of traditional PI controllers, such as overshoot, response time, and static error; IP (integral–Proportional) controllers is replaced instead of the PI to control rotor current d – q components ( I rd and I rq ) in a Park frame through AC–DC–AC converter. A comparative experimental study was implemented to improve the power quality using L, LC & LCL passive filters between the DFIG's rotor circuit and the inverter. Experimental results prove that the proposed DPC under stand-alone mode with LCL-Type filter could operate in several conditions despite the sudden wind speed variations. It improves the unity power factor grid operation ( ≈ 0.98), dynamic responses, and the decoupled power control with high wind power performances: good reference tracking, short response time, neglected overshoot, and low power error. The power quality injected into the RL-load satisfied the limit specified by IEEE harmonic standard 519 (less than 5%). Highlights: Robust DPC based on the IP controller for WECS-DFIG under stand-alone mode is presented in the paper. Real-time validation of proposed DPC strategy under wind speed Change and rotor currents references (Ird* and Irq*) variation are tested and proved with high performances in transient and steady states. Improving power quality injected to the RL-Load is tested and validated (using an LCL-Type filter between the rotor-circuit of DFIG and DC–AC converter). A detailed experimental study of WECS based on DFIG via dSPACE1103 is validated under severe work conditions; to prove the feasibility of the proposed control. Implementation simplicity, few switching losses, fast dynamic response, and good power quality injected to the RL-load; are the mains advantages of the proposed control system.